Small ruminant community-based breeding integrated in the undergraduate curriculum of 23 Ethiopian universities, creating new opportunities for scaling - CGIAR Research Program on Livestock (2021)
Community-based breeding programs (CBBP) developed and implemented by the International Center for Agricultural Research in the Dry Areas (ICARDA) and partners have become an accepted strategy of choice for small ruminant genetic improvement in Ethiopia. In 2021, 23 Ethiopian Universities formally integrated the breeding strategy and related technical material in their animal breeding curriculum at the bachelor’s degree level. This sets the stage for greater availability of skilled professional breeders to scale up CBBP in Ethiopia.